Clearance seal compressors with linear motor drives part II: experimental evaluation of an oil-free compressor - Dadd, M; Liang, K; Stone, C; Bailey, P (SAGE Publications, 2013)
Oil-free compressors are required for various applications, including cryocoolers and refrigeration systems that use compact evaporators. A novel low-cost moving magnet oil-free linear compressor is described here, and follows a companion paper on the linear motor system. The experimental apparatus to evaluate the thermodynamic performance of the linear compressor is comparatively straightforward, but the data analysis is involved, since key measurements have to be corrected for the phase response of the transducers. Harmonic fitting, using fast Fourier transform with zeropadding and minimisation algorithms, have been used for the voltage, current and displacement signals. This enables corrections to be made for the phase lag in the voltage, current and displacement measurements. The experiments using nitrogen, with a constant pressure ratio, show that the linear motor system under resonance achieves a high overall efficiency. For the design point, the motor efficiency is 74%, while for a pressure ratio of 3.0, the average overall adiabatic efficiency is 54% and the isothermal efficiency is 46%, all of which are within a reasonable range for a small compressor.